2006
DOI: 10.3201/eid1206.051235
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Infection in Humans and Horses, Cuba

Abstract: A surveillance system to detect West Nile virus (WNV) was established in Cuba in 2002. WNV infection was confirmed by serologic assays in 4 asymptomatic horses and 3 humans with encephalitis in 2003 and 2004. These results are the first reported evidence of WNV activity in Cuba.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 14 publications
1
25
0
7
Order By: Relevance
“…[4][5][6]11,12 Dengue virus can circulate in sylvatic cycles involving non-human primates and can therefore be considered zoonotic; however, most transmission occurs in urban cycles involving only humans and mosquitoes. Nevertheless, the importance of this virus as a major vector-borne pathogen justified its inclusion in this study and the high degree of seroprevalence observed is consistent with previous studies showing the hyperendemic nature of its circulation in the Caribbean.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]11,12 Dengue virus can circulate in sylvatic cycles involving non-human primates and can therefore be considered zoonotic; however, most transmission occurs in urban cycles involving only humans and mosquitoes. Nevertheless, the importance of this virus as a major vector-borne pathogen justified its inclusion in this study and the high degree of seroprevalence observed is consistent with previous studies showing the hyperendemic nature of its circulation in the Caribbean.…”
Section: Discussionmentioning
confidence: 99%
“…11 This paucity of viral isolations could be the result of a combination of reduced avian mortality, reduced viral loads within avian hosts, or limited mosquito testing. In addition to observation of reduced avian mortality in Mexico, the Caribbean, and Central and South America, serosurveys of equids have demonstrated evidence of spillover transmission 32,34,35,[40][41][42] without documented equine disease, until reaching the temperate latitudes of Argentina. 43 A number of theories could explain reduced virulence.…”
Section: Discussionmentioning
confidence: 99%
“…These rates are significantly higher than the 4.0% (8 of 200 unvaccinated horses) observed in a previously unpublished study (referred to in Komar and Clark, 2006) in 2004 in Trinidad. It is also higher than the rate reported for horses in Venezuela (4.5%; Bosch et al 2007) and Cuba (9.0%; Pupo et al 2006), but lower than in Mexico (29.5-62.5%;Blitvich et al 2003b;Marlenee et al 2004;Alonso-Padilla et al 2009), Guatemala (42.3%;Morales-Betoulle et al 2006), and Guadeloupe (61.6%; Quirin et al 2004). Komar and associates (Komar et al 2003) suggested that the differences in seroprevalence among locations in South and Central America may be a consequence of the difference in the length of time the virus has been in circulation.…”
Section: Discussionmentioning
confidence: 67%